EFEKTIVITAS PROGRAM PENGEMBANGAN KAWASAN PESISIR TANGGUH (PKPT) DI KABUPATEN PEKALONGAN - R., Munna Rafika; Lestari, Hesti (Journal of Public Policy and Management Review, 2018)
This research aims to analyze the efektiviness program execution by looking at the purpose of the has been reached Coastal Area development program Tough (PKPT) which was carried out in three villages namely, Api-api, Pecakaran and Mulyorejo. This research uses qualitative data collection techniques through indepth interviews. In this research the theory used is the theory of public administration, public policy and effectiveness. This program PKPT is urgently needed by coastal communities in particular. Effectiveness can be felt in what has planned in accordance with the results obtained. The participation of coastal communities is indispensable in this program, because the society became the main actors in the implementation of activities. This research has concluded that the implementation of the Program of development of the coastal area is Tough in Pekalongan in particular with the aim to improve the preparedness of communities, improve the quality of the living environment in coastal areas, facilitate development activities the development of socio-economic facilities and infrastructure in coastal regions, develop institutional society as participatory by involving the role of women has not been effective in suspending and standaloned coastal communities. Recommendations for this Audit program, the Government is increasing the return of socialization to society not only to coastal communities (KMP), other recommendations the Government should review again the importance of this work PKPT program.